Preventive Effect of MG-132 on Monocrotaline Induced Pulmonary Hypertension in Rat Pulmonary Artery Hypertension Model - Tafseel Hussain, M Adeel Alam Shah, Farhat Humayun, Sajjad Ghani, Saira Mushtaq, Laraib Imdad, Li Man Xiang, Xinming Xie (Pakistan Journal of Medical & Health Sciences, 2022)
Aim of Study: To Prevent the Monocrotaline induced extracellular matrix remodeling of pulmonary artery by inhibiting Ubiquitin Proteasome System in rat pulmonary artery hypertension model. Study Design: Experimental Study Place and Duration of Study: Xi’an Jiaotong University, Animal experiment center Xi’an China, from January 2016 to July 2018. Materials and Methods: Thirty-three male Sprague-Dawley rats were divided in to three groups namely control group, Monocrotaline (M.C.T) induced group and M.G-132 (a proteasome inhibitor) treated group. The pulmonary artery hypertension (P.A.H) model was established by giving intraperitoneal injection of Monocrotaline (M.C.T) furthermore the M.G-132 was given to hold back proteasome function. The right ventricular systolic pressure (R.V.S.P) and the right ventricular hypertrophy index (R.V.H.I) were used to assess the progress developing P.A.H. Vascular remodeling was determined by H&E staining and the level of ubiquitinated-PTEN protein was measured by Immunoblotting. Results: The final results revealed that the M.C.T increased R.V.S.P and R.V.H.I in rats, whereas these alterations were concealed in P.A.H induced rats which were treated by M.G-132. Also the Zymograghy results in control vs. experimental group revealed that the activity of Matrix metalloproteinase (MMP2/9) in the PAH model group was considerably elevated at (P<0.05), while treatment of M.G-132 in M.C.T-induced P.A.H-rats decreased the activity of MMP2/9 at (p<0.05). Conclusions: However, further in-depth investigations are need of a time to explore the transformations of ubiquitin proteasome & MMP activity in chronic MCT induced-pulmonary artery hypertension model.